Suspended Material and Solute Concentration in Flash Flood Water of Luni River and its Tributaries - Choudhari, J S; Sharma, K D; Vanganai, N S (Annals of Arid Zone, 2016)
Suspended material and chemical composition of the flood water of the Luni river and its tributaries draining an area of about 34, 866 km2 in arid part of western Rajasthan reveals that, suspended sediments were two to three times higher during flood (5830-13920 Cumec) than during low flows (495 to 1192 Cumec). Solute concentration show reverse trend because of dilution, to that of suspended sediment. Lithology of the area controls the sodium, potassium, calcium and mangnesium concentrations during flows.